Characterization of collagenase 3 (MMP-13) expressions in skin melanoma, breast cancer and cervical cancer in vitro - Mat Alewi, Nur Aizura; Abdull Rasad, Mohammad Syaiful Bahari (International Association of Computer Science & Information Technology Press, 2013)
Matrix metalloproteinases (MMPs) comprise of a family of secreted and membrane-bound endopeptidases that hydrolyze extracellular matrix proteins. MMPs are one of many proteins which are undergoing scientific analysis in order to discover their therapeutic potentials. Collagenase 3 (MMP-13), a type of collagenase from the MMP family, has been previously reported to be involved in the development and metastasis of cancers. However, the depth of its involvement in the underlying molecular mechanisms of cancer remains to be poorly known. This study aims to determine the degree of MMP-13 protein expressions in several human cancer cell lines and to ascertain its probable involvement in cancer development. From the study, it was hypothesized that the expression of MMP-13 are varied in several human cancer cell lines (MCF-7, HeLa and A375) and that its expression plays an important role in cancer progression and thus, by understanding such interactions, targeted therapeutic treatments could be developed over time. The quantitative expressions of MMP-13 in skin melanoma (A375), breast cancer (MCF-7) and cervix cancer (HeLa) cells were evaluated through ELISA test. The results showed a marked expression of MMP-13 proteins in MCF-7 (12900 pg/ml), followed by HeLa (8109 pg/ml) and A375 (7515 pg/ml). A375 showed the least amount of expression, which is supported by the fact that only certain forms of skin cancer have been found to express a significant amount of MMP-13. Overall, although variations were found in the expression of the collagenase in various human cancer cell lines, the results depict a prominent presence and probable involvement of MMP-13 in cancer.